2014
DOI: 10.1097/sih.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Using Simulation to Study Difficult Clinical Issues

Abstract: Simulation is a useful research methodology for studying activities difficult to assess in the actual clinical environment such as prenatal counseling at the limits of viability. Dutch subjects were more directive in their approach than their American counterparts, offering fewer options for care and advocating for less invasive interventions. American subjects were more likely to offer a wider range of therapeutic options without providing a recommendation for any specific option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Among the studies included in the review, there were five randomized studies [ 28 , 30 32 , 34 ] and four nonrandomized studies [ 26 , 27 , 29 , 33 ]. As reported in Table 2 , two randomized studies [ 30 , 31 ] did not reveal significant risks of bias based on the Cochrane quality assessment tool [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the studies included in the review, there were five randomized studies [ 28 , 30 32 , 34 ] and four nonrandomized studies [ 26 , 27 , 29 , 33 ]. As reported in Table 2 , two randomized studies [ 30 , 31 ] did not reveal significant risks of bias based on the Cochrane quality assessment tool [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment of nonrandomized studies based on the MINORS tool [ 25 ] is also reported in Table 2 . More in detail, all the nonrandomized studies [ 26 , 27 , 29 , 33 ] clearly described the aim (item 1). Only one study considered a consecutive sample of participants, while the others focused on a convenience sample or did not report the information (item 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Opinions on how to perform prenatal counseling diverge among individual professionals [21, 22, 28]. Earlier, it has been demonstrated that actual prenatal counseling practices appear to be very heterogeneous, within and between countries [1, 6, 12–14, 34, 37, 50]. However, since the outcome of counseling has major impact on life or death decisions, practice variation is unwanted when it is not based on fetal or parental characteristics.…”
Section: Introductionmentioning
confidence: 99%